Tribal education in India - Singh, Bhupinder; Mahanti, Neeti (New Delhi, India, Inter-India Publications, 1995)
Edited version of papers presented at the National Workshop on Tribal Education in India, organised at India International Centre, New Delhi on 14th-15th Oct. 1993
Keywords: India.-- Scheduled tribes.-- Education.-- Congresses; People with social disabilities.-- Education.-- India; Scheduled tribes in India.-- Education; Conference papers and proceedings